Using dense locality sampling resolves the subtle genetic population structure of the dispersive fish species Plecoglossus altivelis. Issue 13 (6th June 2016) - Takeshima, Hirohiko; Iguchi, Kei'ichiro; Hashiguchi, Yasuyuki; Nishida, Mutsumi
Abstract: In dispersive species with continuous distributions, genetic differentiation between local populations is often absent or subtle and thus difficult to detect. To incorporate such subtle differentiation into management plans, it may be essential to analyse many samples from many localities using adequate numbers of high‐resolution genetic markers. Here, we evaluated the usefulness of dense locality sampling in resolving genetic population structure in the ayu ( Plecoglossus altivelis ), a dispersive fish important in Japanese inland fisheries. Genetic variability in, and differentiation between, ayu populations around the Japan–Ryukyu Archipelago were investigated in 4746 individuals collected from 120 localities by genotyping 12 microsatellite markers. These individuals represented the two subspecies of ayu, namely the Ryukyuan subspecies ( Plecoglossus altivelis ryukyuensis ) and both amphidromous and landlocked forms of the nominotypical subspecies ( P. a. altivelis ) along the archipelago. We successfully detected an absence of genetic differentiation within the landlocked form and subtle but significant differentiation and clear geographic patterns of genetic variation among populations of the amphidromous form, which had been considered genetically homogeneous. This suggests that dense locality sampling effectively resolves subtle differences in genetic population structure, reducing stochastic deviation in the detection of genetic differentiation and geographic patterns in local populations of this dispersive species. Resampling analyses based on empirical data sets clearly demonstrate the effectiveness of increasing the number of locality samples for stable and reliable estimations of genetic fixation indices. The genetic population structure observed within the amphidromous form provides useful information for identifying management or conservation units in ayu.